The robust dynamical contribution to precipitation extremes in idealized warming simulations across model resolutions. Issue 8 (17th April 2014) - Lu, Jian; Ruby Leung, L.; Yang, Qing; Chen, Gang; Collins, William D.; Li, Fuyu; Jason Hou, Z.; Feng, Xuelei
Abstract The impact of the circulation shift under climate warming on the distribution of precipitation extremes and the associated sensitivity to model resolution are investigated using Community Atmosphere Model Version 3.0 in an aquaplanet configuration. The response of the probability density function of the precipitation to a uniform sea surface temperature warming can be interpreted as superimposition of a dynamically induced poleward shift and a thermodynamically induced upward shift toward higher intensities, which give rise to manyfold increase in the frequency of the most extreme categories of the precipitation events at the poleward side of the midlatitude storm track. Coarser resolutions underestimate not only the intensity of the precipitation extremes but also the dynamical contribution to the increase of precipitation extremes. Meanwhile, the thermodynamic contribution to the intensification of the precipitation extremes is substantially less than expected from the Clausius‐Clapeyron relation, implicative of significant change in the vertical structure of the precipitation processes.